uspB, a New ς(S)-Regulated Gene in Escherichia coli Which Is Required for Stationary-Phase Resistance to Ethanol - Farewell, Anne (American Society for Microbiology, 1998)
The open reading frame immediately upstream of uspA is demonstrated to encode a 14-kDa protein which we named UspB (universal stress protein B) because of its general responsiveness to different starvation and stress conditions. UspB is predicted to be an integral membrane protein with at least one and perhaps two membrane-spanning domains. Overexpression of UspB causes cell death in stationary phase, whereas mutants of uspB are sensitive to exposure to ethanol but not heat in stationary phase. In contrast to uspA, stationary-phase induction of uspB requires the sigma factor ς(S). The expression of uspB is modulated by H-NS, consistent with the role of H-NS in altering ς(S) levels. Our results demonstrate that a gene of the RpoS regulon is involved in the development of stationary-phase resistance to ethanol, in addition to the regulon’s previously known role in thermotolerance, osmotolerance, and oxidative stress resistance.